Herbert Corey papers - Corey, Herbert, 1872-1954.
Correspondence, diaries, datebooks, literary manuscripts, notebooks, family Bible, clippings, printed matter, photographs, and other papers relating chiefly to Corey's activities as an author and as a journalist in Europe during World War I. Also documents his work as a contributing editor of the Nation's Business, cowboy, sheepherder, and stage driver. Includes material pertaining to Corey's books, Truth about Hoover (1932) and Submarine: The Autobiography of Simon Lake as Told to Herbert Corey (1938), and to the Corey family.
Library of Congress Prints and Photographs Division.
Journalist and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Hoover, Herbert, -- 1874-1964.; Lake, Simon, -- 1866-1945.; Corey family; Nation's business; Cowboys -- West (U.S.); Frontier and pioneer life -- West (U.S.); Journalism; American literature; Sheepherding -- West (U.S.); Stagecoaches -- West (U.S.); Submarines (Ships); World War, 1914-1918 -- Journalists; Authors; Journalists